Are statins beneficial for primary prevention in adults with an elevated hs‐CRP and an intermediate Framingham CVD risk score?. Issue 6 (June 2017) - Mackey, Annamarie; Hoock, Jennifer
Abstract : EVIDENCE‐BASED ANSWER : Statin therapy for cardiovascular primary prevention significantly reduces morbidity and mortality (estimated 5‐year number needed to treat [NNT] between 18 and 40) in adults with an intermediate Framingham cardiovascular risk score and a high‐sensitivity C‐reactive protein (hs‐CRP) level ≥2 mg/L (SOR: B, RCT and systematic review of prospective cohort studies).